Knowledge and Prevention Behavior of Post-COVID-19 Vaccination - Ni Putu Ayu Wulan Noviyanti; Putu Ratna Suprima Dewi; Ni Putu Eka Febianingsih (Babali Nursing Research, 2022)
Introduction: Vaccination is one part of COVID-19 prevention to provide immunity against virus that is being targeted. People who have been vaccinated against COVID-19 should continue to carry out prevention behavior towards COVID-19. This study aims to determine the knowledge and prevention behavior towards COVID-19 in people who have received the COVID-19 vaccine. Methods: Observational research with cross sectional design. Respondents in this study are 78 people who are aged > 18 years living in Badung Regency, obtained by convenience sampling. Respondents filled out the questionnaires by self-administered on the link that had been shared. Descriptive statistical analysis and Chi-Square test were used in data analysis. Results: 62.8% of respondents are female. The average age of the respondents were 28.9 ± 8.1 years, 73.1% in the 20-31 years (age) group. 84.6% with college education, 67.9% as private employees, 100% do not have an underlying disease and 93.6% do not smoke. 78.2% of respondents have a good level of knowledge and 44.9% of respondents behave obediently in carrying out COVID-19 prevention. There are differences in COVID-19 prevention behavior between respondents based on knowledge level (p=0.011), gender (p=0.005) and education level (p=0.033). Conclusion: There are differences in compliance behavior in carrying out COVID-19 prevention between respondents who have good and poor knowledge, and based on characteristics such as sex and education level.